Applying activity theory to undergraduate medical curriculum reform: Lessons in contradictions from multiple stakeholders' perspectives. (3rd July 2022) - Law, Marcus; Veinot, Paula; Mylopoulos, Maria; Bryden, Pier; Brydges, Ryan
Abstract: Purpose: Medical school curricula require regular updating. We adopted an activity theory lens to conduct a holistic, multiple stakeholder-informed analysis of curricular reform, aiming to understand how the social relations between groups contribute to unanticipated tensions and outcomes. Methods: A research assistant conducted semi-structured interviews with purposively sampled ( N = 19) administrative staff, faculty course leads, faculty tutors, curriculum developers, change leaders and student leaders. The team applied a framework analysis to guide within and between stakeholder comparisons. Results: Participants reported unique ( N = 21) and cross-cutting ( N = 17) contradictions underscoring emerging drivers of current and potential change. Unique contradictions raised by 1–2 groups represented seeds of change that had the potential to spread across all groups. By contrast, two general types of cross-cutting contradictions arose when one group had a dominant, confirming voice or two or more groups had contrasting perspectives. Conclusions: While finding contradictions was expected, our analysis profiled their nature and some of the specific tensions they raised across and within stakeholder groups. The activity theory lens provided an accessible way to unravel curricular reform into manageable units of analysis. Systematically identifying contradictions arising from curricular reform will help stakeholders collaborate with a shared purpose toward positive, sustained change.